2016
DOI: 10.1159/000444803
|View full text |Cite
|
Sign up to set email alerts
|

Four Neuroendocrine Tumor Types and Neuroendocrine Carcinoma of the Duodenum: Analysis of 203 Cases

Abstract: Background: Several types of neuroendocrine neoplasms (NENs) have been described in the duodenal tract, from low-grade tumors (NETs) to high-grade neuroendocrine carcinomas (NECs). A comprehensive analysis of histology, hormonal profile and prognostic parameters of a sufficiently large duodenal NEN series to cover all main kinds of neoplasms is however lacking. Methods: We collected a retrospective series of 203 duodenal wall and ampullary region NENs, from six specialized endocrine pathology centers. All were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
110
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(124 citation statements)
references
References 30 publications
9
110
2
3
Order By: Relevance
“…However, the WHO 2010 classification did not regard this as a prognostic factor possibly because of enormous inter-observer differences among pathologists in identifying the presence of LVI [1,26]. However, the recent study showed that LVI is one of the risk factors for LN metastasis in D-NET [21]. This study firstly demonstrates LVI as a risk factor for metastasis in NAD-NET measuring ≤20 mm in diameter.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, the WHO 2010 classification did not regard this as a prognostic factor possibly because of enormous inter-observer differences among pathologists in identifying the presence of LVI [1,26]. However, the recent study showed that LVI is one of the risk factors for LN metastasis in D-NET [21]. This study firstly demonstrates LVI as a risk factor for metastasis in NAD-NET measuring ≤20 mm in diameter.…”
Section: Discussionmentioning
confidence: 79%
“…NAD-NETs >20 mm in diameter were known as a risk factor for metastasis [7,10,12,21]. However, in NAD-NETs ≤20 mm in diameter, the therapeutic approach of individual patients still remains in dispute [7,12,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Grozinsky-Glasberg et al [36] found primary tumor size of ≥1 cm in all of the 20 (locally or distantly) metastatic cases they collected (out of 254 patients scrutinized, 7.9%) with, however, a Ki67 index of between 3 and 20% (i.e., G2) in only 6 out of the 17 metastatic cases investigated. In our type I NETs, G2 failed to be associated with gastric wall invasion or metastases, despite the fact that an association of grade with tumor behavior as well as patient outcome was ascertained for type III gastric NETs, as well as for pancreatic and duodenal NETs [39-41]. These results bring the attention to previous type I NET series where G2 failed to predict tumor behavior [27, 42] or showed no apparent impact on tumor behavior and patient survival despite a high G2 type I NET percentage (71% reported by Lee et al [29] and 34% by Campana et al [43]).…”
Section: Discussionmentioning
confidence: 99%
“…Da selbst kleine Gastrinome < 1 cm häufig metastasieren, ist eine endoskopische Behandlung nicht adäquat [233], s. auch Erläuterungstext zu Empfehlung 3.10.…”
Section: Starke Empfehlung Starker Konsensunclassified